2007
DOI: 10.1186/1477-7819-5-20
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal stromal tumor of the anal canal: an unusual presentation

Abstract: At the moment, only ten cases of c-kit positive anal GIST are reported in the literature. These few data are not sufficient to establish a widely accepted approach for this neoplasia. We recommend to perform an initial local excision, to define the risk of aggressive behavior and the resection margins and proceed to a more aggressive treatment, if the GIST belongs to high or very high risk group. The role of adjuvant therapy is still uncertain. Although inhibitors of tyrosine-kinase receptor needs further stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 22 publications
(21 reference statements)
1
17
0
5
Order By: Relevance
“…La protéine c-kit est un récepteur transmembranaire dont le ligand est un facteur de croissance. Dans les cellules exprimant le gène c-kit muté, l'activation non régulée de la protéine est à l'origine d'une prolifération cellulaire incontrôlable aboutissant à l'apparition d'une tumeur [1,[6][7][8].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La protéine c-kit est un récepteur transmembranaire dont le ligand est un facteur de croissance. Dans les cellules exprimant le gène c-kit muté, l'activation non régulée de la protéine est à l'origine d'une prolifération cellulaire incontrôlable aboutissant à l'apparition d'une tumeur [1,[6][7][8].…”
Section: Discussionunclassified
“…Les autres localisations, notamment anorectales, sont rares, représentant 5 % environ de l'ensemble des localisations [1,6].…”
Section: Discussionunclassified
“…They arise from the interstitial cells of Cajal and they account for 0.1 % to 3 % of all G.I malignancies [2]. The site distribution of these tumours is as follows: Esophagus (3 %-5 %),stomach(60 %), small intestine(25 %-30 %), colon and rectum(1 %-5 %),others(2 %-6 %)- [1][2][3]. Gastrointestinal stromal tumors of the small intestine presenting with perforation can be found as isolated reports [5,8].…”
Section: Discussionmentioning
confidence: 99%
“…They commonly originate in the stomach, followed by small intestine [1][2][3][4]. They rarely arise in the caecum, with the entire colon and rectum contributing to less than 5 % of all GISTs [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been suggested that ICC or their precursor matrix mesenchymal cell may be the origin of the stroma tumors. Therefore, GIST are sometimes called the gastrointestinal pacemaker cell tumors (GIPACT) (4,5,(14)(15)(16)(17).…”
mentioning
confidence: 99%